Mitochondrial COI gene-based phylogenetic and haplotype analysis of Manouria emys from Sumatra, Indonesia - ASHRIFURRAHMAN ASHRIFURRAHMAN; SYAIFULLAH SYAIFULLAH; DEWI IMELDA ROESMA; DJONG HON TJONG; INDRI LESTARI (Society for Indonesian Biodiversity, 2025)
Abstract. Ashrifurrahman, Syaifullah, Roesma DI, Tjong DH, Lestari I. 2025. Mitochondrial COI gene-based phylogenetic and haplotype analysis of Manouria emys from Sumatra, Indonesia. Biodiversitas 26: 6224-6231. Genetic and phylogenetic analyses are essential for understanding the evolutionary relationships and genetic variation of the critically endangered Manouria emys, particularly in Indonesia, where molecular data remain limited. This study aimed to determine the phylogenetic placement and haplotype diversity of M. emys from Sumatra, Indonesia representing the first COI record from this region. A single sample collected from West Sumatra was analyzed through DNA extraction, PCR amplification of the COI (Cytochrome Oxidase Subunit I) gene, and sequencing. An 886 bp COI gene fragment was confirmed as M. emys through sequence similarity analysis and subsequently aligned with 29 global reference sequences for phylogenetic and haplotype analyses. Phylogenetic analysis using the Maximum Likelihood method showed that the Sumatran sample clustered within the M. emys emys clade, together with sequences from Borneo and the Taipei Zoo. Three subclades were observed within M. emys, corresponding to M. emys emys, M. emys phayrei, and one distinct genetic lineage of unconfirmed subspecies status. The analysis showed low genetic divergence within each subspecies but relatively high differentiation between M. emys and the outgroup. Haplotype analysis identified three main haplogroups, with the Sumatran sample showing close genetic affinity to M. emys emys from Borneo. The presence of multiple M. emys emys haplotypes reported from India may reflect population movement or human mediated translocation, highlighting the need for broader regional studies. This study provides the first molecular evidence of M. emys from Sumatra, offering a valuable genetic reference for future research, conservation management, and monitoring of wildlife trade involving this critically endangered tortoise.